Mechanisms Reducing the Level of Reversible Benefits in Unit-Linked Life Insurance Contracts. A Legal and Economic Analysis - Pacud , Radosław (Studia Oeconomica Posnaniensia, 2018)
The subject of the article is the economic and legal analysis of consumer rights in the situation of the early termination of life insurance. A market analysis of the mechanisms of liquidation fees or contractual redemption values was conducted, and then these appraisals were evaluated in the light of the growing number of court disputes. An analysis of the distribution of potential benefits and losses between the parties to the insurance contract gave grounds for observing the contractual imbalance, which generates higher contractual risk for the consumer in the case of mechanisms reducing the level of returnable payment. It was found that the rates of liquidation fees and redemption values determining the returnable payment at a level lower than 70-80% of the value of participation units as of the date of termination of the contract provide the Insurance Company with additional benefits, the implementation of which may be perceived as an abuse of law within the meaning of Article 5 of the Polish Civil Code.